On the Draft Law for Information Center Personnel Bilgi Merkezleri Çalışanları Kanun Tasarısı Taslağı Üzerine - Osman Tahsin Öcal (Türk Kütüphaneciliği, 2010)
Technical staff pattern for Information Centers Personnel, which is widely discussed nowadays, is valuated by defining modern information centers. It is emphasized that it is a necessity to consider the draft legal amendment together with the related legislation and situation in libraries and information centers within educational institutions and state institutions and organizations. It is asserted that a Law for Information Centers Personnel, compatible to the needs of information age, will emerge by taking into consideration the national and international professional standards. Günümüzde tartışılmakta olan Bilgi Merkezleri Çalışanları için teknik kadro yaklaşımı çağdaş bilgi merkezlerinin tanımı yapılarak değerlendirilmektedir. Tasarlanan yasal değişikliğin ilgili mevzuat, eğitim kurumları ve kamu kurum ve kuruluşları bünyesindeki kütüphane ve bilgi merkezlerindeki durum ile birlikte ele alınmasının gerekliliğine değinilmektedir. Ulusal ve uluslararası mesleki standartlar gözetilerek bilgi çağının gereksindiği bir Bilgi Merkezleri Çalışanları Kanununun ortaya çıkacağı savunulmaktadır.